Ambient Ole e 1 Aeroallergen and Pollen Counts of Olea europaea L. from 2009 until 2011 in Évora (South Portugal) - C. M. Antunes (2013)
These resulls show thal Ole e 1 is preferenlially associaled wilh pollen grains, allhough a small percenlage may also be found in submicronic particies. It was recorded a yeariy variation in airborne pollen and Ole e1. The highesl polency pollen and the highesl allergen index were recorded in 2010, a season wllh lhe lowesl pollen index. ln conclusion, aeroallergen quanlification may contribute togelher with airbome pollen counts, to a betler understanding 01 lhe exposure leveis lo airbome pollen allergens. Acknowledgments: This study is integraled in the European project HIALlNE (Executive Agency for Health and Consumers, grant agreemenl No 20081107)